2020
DOI: 10.3892/etm.2020.9411
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the pathogenic fungi in patients with superficial mycosis in the Northeastern China during 10 years

Abstract: This study analyzed the infection of superficial mycosis and the relationship between the distribution characteristics of pathogenic fungi and age, time and sex in Northeast China in the past 10 years. We would like to provide a theoretical basis for the diagnosis and treatment of related diseases. From December 2008 to December 2018, 5,374 superficial mycoses from Northeast China were selected. The fungal species were identified by fungal microscopy, fungal culture, and species identification. Besides, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…We reported that dermatophytosis was the second common type of SFI (34.8%), which is in line with previous studies 7 . However, in epidemiologic studies in China, Turkey, and Germany, 82%, 74%, and 83.2% of dermatophytosis were reported, respectively 26,28,31 . In this study, the nails were the most affected anatomic site in the patients, as similarly reported in Egypt and Southern China 18,27 .…”
Section: Discussionsupporting
confidence: 91%
“…We reported that dermatophytosis was the second common type of SFI (34.8%), which is in line with previous studies 7 . However, in epidemiologic studies in China, Turkey, and Germany, 82%, 74%, and 83.2% of dermatophytosis were reported, respectively 26,28,31 . In this study, the nails were the most affected anatomic site in the patients, as similarly reported in Egypt and Southern China 18,27 .…”
Section: Discussionsupporting
confidence: 91%
“…Other classification systems, based on phenotypes, genetic relationships, and molecular criteria, are more complicated and less used in the clinical setting ( Gnat et al., 2019 ). Apart from dermatophytes, yeasts and molds have also been shown to cause superficial mycosis, with the elderly reportedly more susceptible to these less common pathogens than the younger population ( Wang et al., 2020b ). A summary of typical development of skin infections is shown in Table 1 .…”
Section: Human Fungal Diseases and Conventional Treatment Modalitiesmentioning
confidence: 99%
“…4 Incidence of fungal infection diseases is higher in men compared to a woman. 5 Fungal infection disease can be classified into two groups, superficial infection and systemic infection. 6 Superficial fungal infection is a fungal infection that affects the surface of the body such as skin, hair, and nails.…”
Section: Introductionmentioning
confidence: 99%
“…(17.40%). 5 The most frequent infection sites of T. rubrum include foot, inguinal, axilla, scalp, and nail. This infection causes mild to moderate dermatological symptoms with a variety of severity.…”
Section: Introductionmentioning
confidence: 99%